RGMb drives macrophage infiltration to aggravate kidney disease - Yonglun Kong; Ming Yue; Chunhua Xu; Jing Zhang; Huiling Hong; Jiahuan Lu; Yang Wang; Xiaoyi Zhang; Qiuju Chen; Chen Yang; Hua-Feng Liu; Jinzhong Qin; et al. (Proceedings of the National Academy of Sciences, 2025)
The importance of macrophages in kidney diseases has been well established; however, the mechanisms underlying the infiltration of macrophages into injured kidneys are not well understood. RGMb is a member of the repulsive guidance molecule (RGM) family. RGMb can be expressed on the cell surface but a large portion of RGMb is localized intracellularly. Among various immune cell types, macrophages express the highest levels of RGMb, but the biological functions of RGMb in macrophages remain largely unknown. We find that RGMb promoted macrophage migration in vitro and that in vivo, RGMb enhanced infiltration of macrophages into injured kidneys and aggravated kidney inflammation and injury in mice. Mechanistically, RGMb bound to TAB1 inside the cell and facilitated the interaction between TRAF6 ubiquitin ligase and TAB1, thereby promoting TRAF6-mediated K63-linked polyubiquitination and phosphorylation of TAK1, followed by increased αTAT1 phosphorylation and α-tubulin acetylation. The resulting changes in the cytoskeleton promoted macrophage migration in vitro and in vivo. Deletion of Rgmb in macrophages markedly reduced TAK1 phosphorylation, αTAT1 phosphorylation, and α-tubulin acetylation and attenuated macrophage infiltration, renal inflammation, tubular injury, and interstitial fibrosis during kidney injury. Our results suggest that macrophage RGMb promotes kidney disease by increasing macrophage infiltration via the TRAF6-TAB1-TAK1/αTAT1/α-tubulin cascade.